Target detection and estimation using a stereo vision camera for autonomous navigation - Chow, Song Qian. (2009)
Stereo based vision cameras are increasingly popular in terms of their usage in the commercial markets. They are relatively inexpensive and can perform an array of functions. Currently, there are many different types of stereo vision cameras available. Such cameras have been used to aid in the navigation of autonomous vehicles like cars and kayaks.